Evaluation of the Performance of the IDvet IFN-Gamma Test for Diagnosis of Bovine Tuberculosis in Spain - de la Cruz, Maria Luisa; Branscum, Adam J.; Nacar, Jesus; Pages, Enrique; Pozo, Pilar; Perez, Andres; Grau, Anna; Saez, Jose Luis; de Juan, Lucia; Diaz, Rosa; Minguez, Olga; Alvarez, Julio (Frontiers in Veterinary Science, 2018)
In Spain, the national bovine tuberculosis (bTB) eradication program is based on yearly skin testing of every ≥6 weeks old animal using the single or comparative tuberculin test and parallel use of the interferon-gamma (IFN-γ) assay as an ancillary diagnostic test in infected herds. There are several versions of the latter. Recently, a new commercial IDvet IFN-γ assay has been authorized for use in the program, but there is limited scientific evidence about its performance in different epidemiological settings. Therefore, two studies to evaluate the performance of the IDvet assay were conducted. In study 1, a concordance analysis between the new IDvet and the Bovigam IFN-γ assay in use in Spain for over 10 years was conducted. In study 2, results from the IDvet assay when applied in tandem with a single intradermal tuberculin (SIT) test were used to evaluate the concordance between both tests and to estimate their sensitivity (Se) and specificity (Sp) using a Bayesian latent-class model. Field data from cattle herds located in Madrid and Castilla y Leon (Spain) were collected. For study 1, herd selection was based on a high expected prevalence of reactors to the IFN-γ assay, while herds were selected at random to estimate Se and Sp of the new IDvet assay in study 2. Agreement between the results obtained with both kits for IFN-γ assay was poor (Kappa= 0.20), and a receiver operating characteristic (ROC) analysis indicated a low Se of the new IDvet relative to the Bovigam in a heavily bTB infected population. The Bayesian latent-class analysis estimated the Se of the IDvet assay to be 36.7% [95% probability posterior interval (PPI) 14.7%-78.8%] with estimated Sp close to 100% when the cut-off recommended by the manufacturer (35) was applied. At the alternative cut-off values of 16 and 4, the estimated Se of the IDvet assay increased to 49.0% (PPI: 24.8-94.1%) and 56.0% (PPI: 30.8-96.3%), respectively, while maintaining a high specificity. The results suggest that the new IDvet assay may have lower sensitivity than the Bovigam for diagnosis of bTB in cattle herds in Spain, and that adjusting its cut-off might be considered.